Making Hardware Removal Unnecessary by Using Resorbable Implants for Osteosynthesis in Children - Pascal Heye; Christoph Matissek; Clemens Seidl; Marcell Varga; Tamas Kassai; Gergö Jozsa; Thomas Krebs (MDPI AG, 2022)
Introduction: Following osteosynthesis, children generally require a second surgery to remove the hardware. This becomes unnecessary, by using resorbable implants. Limiting the number of required surgeries and their associated risks, this technique provides critical aspects of minimally invasive surgery. This review focuses on resorbable implants for osteosynthesis for the treatment of fractures in children and discusses their clinical features. Method: We provide an overview of the two most common technologies used in resorbable osteosynthesis materials: polymer- and magnesium-based alloys. Clinical examples of osteosynthesis are presented using polymer-based ActivaTM products and magnesium-based Magnezix® products. Results: Polymer-based implants demonstrate surgical safety and efficacy. Due to their elasticity, initial placement of polymer-based products may demonstrate technical challenges. However, stability is maintained over the course of healing. While maintaining good biocompatibility, the rate of polymer-resorption may be controlled by varying the composition of polyesters and copolymers. Similarly, magnesium-based implants demonstrate good mechanical stability and resorption rates, while these characteristics may be controlled by varying alloy components. One of the significant shortcomings of magnesium is that metabolism results in the production of hydrogen gas. Both technologies provide equally good results clinically and radiographically, when compared to non-resorbable implants. Conclusion: Resorbable osteosynthesis materials demonstrate similar therapeutic results as conventional materials for osteosynthesis. Resorbable implants may have the potential to improve patient outcomes, by sparing children a second surgery for hardware removal.